Translingual practices with 9th graders: living the language (2019)
In this paper, we depict a qualitative case study around translingual practices and students’ perceptions about them. We traced the importance of recognizing the use of both languages into the Colombian context since it seemed the government has restricted our Mother Tongue (MT) in the students’ language learning process due to several reasons. We related this situation to how students learn the Target Language (TL/English) without letting behind their MT (Spanish). Although there have been several studies abroad, there have been few studies in Colombia about the use of both languages known as Translanguaging or translingual practices. That is why this study aimed to characterize how ninth graders develop Translingual Practices and to reveal how ninth graders perceive the use of the MT while learning the TL. We conducted this study at a public school on the downtown of Bogota, and the data was collected from 12 ninth graders, bearing in mind the task-based approach as the one in which they had the opportunity to express themselves through written texts. Considering the findings after an exhaustive interpretation through the Grounded theory approach, we posed those translingual practices as practices where they could “Live the Language” because they took advantage of their linguistic repertoire as a making-meaning tool and as a confidence strategy for them.